Le partage de quels savoirs ? Les articles Wikipédia comme objets-frontières - Maude GAUTHIER; Kim SAWCHUK (Tic & Société)
Wikipedia promotes itself as a community that anyone can join as long as they know the rules. In this paper, we reflect on our attempt to join this community and to edit entries on age and ageing so that they include an intersectional perspective. Sharing our knowledge seemed necessary because feminist and ageing studies often stay underrepresented outside the academy. Noticing such gaps in Wikipedia, we decided to contribute to this knowledge common and attend to issues of governance that came up during our interventions. Rather than being a simple exercise in making academic research “vernacular,” our excursion into the world of writing Wikipedia entries reveals how certain entries act as boundary objects, sites of contestation between different communities of practice. We analyze the discussions around the creation of entries for the Centre for Women, Ageing and Media, and for Technologies et vieillissement.